2003
DOI: 10.1073/pnas.1831512100
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosyl- l -methionine is an effector in the posttranscriptional autoregulation of the cystathionine γ-synthase gene in Arabidopsis

Abstract: Cystathionine ␥-synthase, the first committed enzyme of methionine biosynthesis in higher plants, is encoded by the CGS1 gene in Arabidopsis thaliana. We have shown previously that the stability of the CGS1 mRNA is negatively regulated in response to methionine application [Chiba, Y., Ishikawa, M., Kijima, F., Tyson, R. H., Kim, J., Yamamoto, A., Nambara, E., Leustek, T., Wallsgrove, R. M. & Naito, S. (1999) Science 286, 1371-1374]. To determine whether methionine itself is the effector of the CGS1 exon 1-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 34 publications
6
117
0
2
Order By: Relevance
“…This fact provides a clear in vivo demonstration that TS This translation arrest triggers CGS mRNA degradation (Onouchi et al 2005). A 5Ј-truncated RNA species are formed as degradation intermediate (Chiba et al 1999;Chiba et al 2003) activity has a key role in regulating the carbon flow into the methionine biosynthetic pathway and, when TS activity is compromised, the regulation of CGS alone is not sufficient. This is in agreement with the finding that antisense repression of the TS gene in transgenic potato resulted in a reduction of TS activity to 6% of wild type and up to 230-fold increase in soluble methionine in leaf and tuber tissues, respectively (Zeh et al 2001).…”
Section: Threonine Biosynthesis Regulates Metabolic Flux To Methioninmentioning
confidence: 98%
See 1 more Smart Citation
“…This fact provides a clear in vivo demonstration that TS This translation arrest triggers CGS mRNA degradation (Onouchi et al 2005). A 5Ј-truncated RNA species are formed as degradation intermediate (Chiba et al 1999;Chiba et al 2003) activity has a key role in regulating the carbon flow into the methionine biosynthetic pathway and, when TS activity is compromised, the regulation of CGS alone is not sufficient. This is in agreement with the finding that antisense repression of the TS gene in transgenic potato resulted in a reduction of TS activity to 6% of wild type and up to 230-fold increase in soluble methionine in leaf and tuber tissues, respectively (Zeh et al 2001).…”
Section: Threonine Biosynthesis Regulates Metabolic Flux To Methioninmentioning
confidence: 98%
“…Interestingly, although TS mRNA and protein levels were normal in mto2-1, accumulation of CGS mRNA and protein were negatively correlated with that of methionine and reduced to approximately 40% of that in wild type (Bartlem et al 2000) (Figure 5B). The reduced levels of CGS associated with methionine over-accumulation showed that the regulatory mechanism controlling CGS mRNA accumulation in response to increased SAM (Chiba et al 1999;Chiba et al 2003) was functioning normally. Methionine was able to over-accumulate 20-fold in mto2-1 when CGS levels were markedly reduced.…”
Section: Threonine Biosynthesis Regulates Metabolic Flux To Methioninmentioning
confidence: 99%
“…In bacteria, AdoMet binds to RNA riboswitches and regulates genes involved in sulfur metabolism (13). In Arabidopsis thaliana, stability of the cystathionine ␥-synthase mRNA is negatively regulated by AdoMet (14), and in HepG2 cells, methionine withdrawal results in an AdoMet-dependent increase in MATII expression by stabilization of its mRNA (15). We excluded an effect of AdoMet on transcription (by Northern analysis and reporter assays using the Ϫ1b CBS promoter, which is most commonly used in liver) and translation (by in vitro transcription͞translation and polysome analysis) (data not shown).…”
Section: Stability Of Cbs Is Decreased Under Conditions Of Methioninementioning
confidence: 99%
“…Most methionine is converted to SAM by SAM synthase in plants [35]. SAM reduces the expression level of GCS in Arabidopsis [36]. SAM acts as a precursor for ethylene and polyamines biosynthesis, which supports tolerance against abiotic and biotic stresses [2,37,38].…”
Section: Discussionmentioning
confidence: 99%